2007
DOI: 10.1177/0021934705285595
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of HIV Knowledge and Testing

Abstract: This research explored the correlates of HIV knowledge and testing. The study predicted that there would be significant relationships between knowledge of HIV transmission, and testing for HIV, educational level, and gender. Testing behavior was also predicted to be associated with gender and knowing someone who has HIV/AIDS or someone who has died of the disease. A convenience sample of 429 respondents in the Republic of South Africa participated in the study. Volunteers completed the Carey and Schroder Brief… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 4 publications
3
11
0
1
Order By: Relevance
“…The observed association between HIV/STI testing and HIV knowledge score in our study was consistent with two other cross-sectional studies, namely Scott-Sheldon LA et al, [18] and Haile BJ et al, 2007 [19]. The cross-sectional study design prevents strong inferences regarding the directionality of this association.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The observed association between HIV/STI testing and HIV knowledge score in our study was consistent with two other cross-sectional studies, namely Scott-Sheldon LA et al, [18] and Haile BJ et al, 2007 [19]. The cross-sectional study design prevents strong inferences regarding the directionality of this association.…”
Section: Discussionsupporting
confidence: 91%
“…The available literature provides little data to allow understanding of how sexually active heterosexual men behave in relation to HIV/STI testing [14]. Third, the few studies on sexually active heterosexual men are often from the West [15, 16] and Africa [1719] where their sexual behaviour and HIV/STI transmission knowledge are likely to be different from that of Asia men [20]. Fourth, to the best of our knowledge, there is no published study that evaluates the factors associated with HIV/STI testing behaviour of heterosexual men patronising entertainment establishments (EEs) who engage in casual or paid sex.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Norman, Devieux, Rosenberg, and Malow (2011) found that those with a history of alcohol, marijuana, and other illicit drug use were more likely to report a history of testing. The finding that females who sought testing opportunities had more knowledge about viral transmission than those who did not seek testing (p = .011) suggests the possibility that, similar to prior research, women who engaged in riskier behaviors may be aware of potential risks, and thus made an effort to determine their status (Haile, Chambers, & Garrison, 2007).…”
Section: Resultssupporting
confidence: 55%
“…Similarly, the evidence regarding the association between HIV knowledge and risky sexual behavior is also mixed. Some studies found a positive relationship between high HIV knowledge, HIV testing and consistent condom use in adolescents [15,16] In contrast, some studies found no associations between HIV knowledge and sexual behaviors [17,18]. …”
Section: Introductionmentioning
confidence: 99%